POLA INTERAKSI ANTARA SISWA DAN GURU DALAM MEMBANGUN PRESTASI BELAJAR MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (STUDI KASUS DI SMP ISLAM MA’ARIF 02 JANTI MALANG) - Muhammad Djamal Ghofiru; Rosichin Mansur; Jazari Jazari (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
Interactions between students and teachers that occur directly in the classroom or outside the classroom must be able to build a learning achievement, where the teacher is able to provide material by inviting students to understand the material provided and able to be applied in daily life. In interactions that run well between students and teachers, students will also produce good achievements. However, there are interactions that are not in line with expectations where the role of the teacher as the material giver is less creative so that the students are not all interested and understand it. The purpose of this study was to describe the pattern of interaction between students and PAI subject teachers, to build learning achievement in PAI subjects, and to describe the results of learning achievement achieved by students of Islamic Education subjects in schools. To achieve these objectives, the researcher carried out with a type of qualitative research. The procedure of data collection is done by using the observation method, which is direct observation to find out research activities phenomena carried out systematically, interview methods which are methods of collecting data by using verbal questions and answers with sources chosen by researchers, and documentation methods that are looking for data about matters, notes, transcripts, books, reports, agendas and so on. Keywords : Islamic Education, Interactions, Teaching and Learning, Achievement